1992
DOI: 10.1093/oxfordjournals.jbchem.a123874
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Renin-Binding Protein Gene Expression in Rats1

Abstract: Rat gene for renin-binding protein (RnBP) was shown to be expressed in the kidney, adrenal gland, brain, lung, spleen, ovary, testis, and heart. On sodium depletion and captopril administration, the rat showed a marked increase in the adrenal RnBP mRNA level and a slight decrease in the kidney RnBP mRNA level. In two-kidney, one clip hypertensive rats, the RnBP mRNA levels of the clipped and contralateral kidneys were unchanged and also its adrenal mRNA level was maintained at the control level. The recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…43 A renin-binding protein has been described in various organs, including the heart. 44 Recently, it was proposed that prorenin becomes catalytically active after binding to a cell receptor. 45 Receptor binding of prorenin would unfold its prosegment, and this renders the active site accessible to angiotensinogen.…”
Section: Discussionmentioning
confidence: 99%
“…43 A renin-binding protein has been described in various organs, including the heart. 44 Recently, it was proposed that prorenin becomes catalytically active after binding to a cell receptor. 45 Receptor binding of prorenin would unfold its prosegment, and this renders the active site accessible to angiotensinogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, such binding and internalization could not generate any angiotensin peptides intracellularly. Besides, existence of renin/prorenin receptor independent of mannose 6-phosphate such as renin binding protein (RnBP), renin/prorenin binding protein (ProBP) in rat tissues, vascular renin binding protein have also been confirmed (Takahashi et al, 1983;Tada et al, 1992;Campbell et al, 1994;Sealy et al, 1996) that bind with different binding affinities to their ligands. Fig.…”
Section: (Pro)renin Receptor a New Family Member Of Renin Angiotensimentioning
confidence: 95%
“…The amino acid sequences were highly similar to each other and were characterized by the presence of a conserved leucine zipper motif (3,13). The expression of rat RnBP was detected mainly in the kidney, considerably in the adrenal gland, brain, lung, spleen, and ovary and slightly in the testes and heart by RNase protection analysis (10). Co-expression of human renin and RnBP cDNA in mouse AtT-20 cells showed that RnBP regulates active renin secretion from the transformant (5).…”
mentioning
confidence: 93%